Highly adhesive polyester film

JP7639980B2Active Publication Date: 2025-03-05TOYOBO CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024166207
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-07
Filing Date
2024-09-25
Publication Date
2025-03-05
Estimated Expiration
2043-11-24

AI Technical Summary

Benefits of technology

【0016】 本発明の易接着性ポリエステルフィルムは、機能層とポリエステルフィルムとの密着性(特に、長時間保管後の密着性等)に優れ、高い密着信頼性を有している。また、耐ブロッキング性、及び透明性も優れている。そのため、光学用途等への広い適用が可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639980000001
    Figure 0007639980000001
  • Figure 0007639980000002
    Figure 0007639980000002
  • Figure 0007639980000003
    Figure 0007639980000003
Patent Text Reader

Abstract

To provide an easy adhesive polyester film excellent in adhesion with a functional layer such as a hard coat layer, an adhesive agent and so on and to provide a laminated polyester film provided with the functional layer.SOLUTION: The present invention relates to an easy adhesive polyester film having a polyester film substrate and a coating layer on at least one side thereof, wherein the coating layer is formed from a composition comprising a polycarbonate polyurethane resin, a polyester resin and inert particles, and both the polycarbonate polyurethane resin and the polyester resin contain a cyclohexane ring in their respective molecules, and at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a highly adhesive polyester film having excellent adhesion to various functional layers, and a laminated polyester film having the functional layers. [Background technology]

[0002] Hard coat films having a transparent hard coat layer laminated thereon are used on the front surfaces of displays such as touch panels, computers, televisions, and liquid crystal display devices, as well as decorative materials, etc. Panel members used in displays are formed by laminating a hard coat film with a polarizer or with other members, and the lamination is performed by applying an adhesive component.

[0003] As the transparent plastic film substrate, a transparent polyester film is generally used, and in order to improve the adhesion between the polyester film substrate and the hard coat layer and adhesive, a coating layer having high adhesion is often provided on the surface of the polyester film as an intermediate layer between them.

[0004] The hard coat film is required to have durability against temperature, humidity, light, etc., transparency, chemical resistance, scratch resistance, antifouling, etc. In addition, since it is often used on the surface of a display or a decorative material, visibility or design is required. Therefore, in order to suppress glare or iridescent color due to reflected light when viewed from any angle, it is common to provide an antireflection layer with a multilayer structure in which a high refractive index layer and a low refractive index layer are mutually laminated on the upper layer of the hard coat layer.

[0005] In recent years, hard coat layers having various compositions have been developed, and the adhesion between the substrate and the hard coat layer has been discussed according to the composition. For example, when a film laminated with a hard coat layer is used for a liquid crystal television display, not only the initial adhesion immediately after lamination but also performance such as resistance to moisture and heat and adhesion retention over time are required in order to ensure high reliability for long-term use.

[0006] The same is true for the adhesive, which is required to have durability against temperature, humidity, light, etc., transparency, chemical resistance, scratch resistance, antifouling, etc. In addition, since it is often used on the surface of a display or decorative material, visibility or design is required. In recent years, adhesives having various compositions have been developed, and the adhesion between the substrate and the adhesive has been discussed according to the composition. For example, when a member bonded with an adhesive is used for a liquid crystal television display, in order to ensure high reliability for long-term use, not only initial adhesion immediately after lamination but also performance such as resistance to moisture and heat and adhesion retention over time are required.

[0007] In a liquid crystal display device, polarizing plates are arranged on both sides of a glass substrate forming the surface of a liquid crystal panel due to its image forming method. A polarizing plate generally has a structure in which a polarizer protective film is attached to both sides of a polarizer made of a polyvinyl alcohol-based film and a dichroic material such as iodine via a hydrophilic adhesive such as a polyvinyl alcohol-based resin. As a protective film used to protect a polarizer, a triacetyl cellulose film has been used so far in terms of optical properties and transparency.

[0008] However, triacetyl cellulose does not have sufficient durability, and when a polarizing plate using a triacetyl cellulose film as a polarizer protective film is used under high temperature or high humidity, the performance of the polarizing plate, such as the polarization degree and hue, may be reduced. In addition, in recent years, there has been a demand for thinner polarizing plates to accommodate thinner displays, but there is a limit to how thin a triacetyl cellulose film can be made from the viewpoint of maintaining moisture barrier properties. Therefore, it has been proposed to use a polyester film as a polarizer protective film having durability and moisture barrier properties (for example, see Patent Document 1).

[0009] The triacetyl cellulose film used as a polarizer protective film has an alkali treatment or the like on its surface, and has an extremely high affinity with a hydrophilic adhesive. Therefore, a protective film made of a triacetyl cellulose film has an extremely high adhesion to a polarizer coated with a hydrophilic adhesive. However, the adhesion of a polyester film to a hydrophilic adhesive is insufficient, and this tendency is particularly pronounced in the case of a polyester film having orientation due to a stretching treatment. Therefore, in order to improve the adhesion to a polarizer or a hydrophilic adhesive applied to a polarizer, it has been reported that a coating layer is provided by coating the surface of a polyester film with a highly hydrophilic material (see, for example, Patent Document 1).

[0010] In the field of conventional highly adhesive polyester films, it has been reported that a laminated polyester film having a coating layer containing a polyester resin using a naphthalene dicarboxylic acid component on at least one side of the polyester film has excellent adhesion to a surface functional layer such as a hard coat layer (see, for example, Patent Document 2).

[0011] In addition, it has been reported that an easily adhesive polyester film having a coating layer on at least one side of the polyester film, which contains a polyurethane resin whose constituent is an aliphatic polycarbonate polyol that has excellent flexibility and adhesion, has excellent adhesion to an optical functional layer under high temperature and high humidity conditions (see, for example, Patent Document 3). Although the adhesion of each of these films has been confirmed, no easily adhesive polyester film having excellent adhesion after long-term storage has been obtained. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2013-063610 A [Patent Document 2] JP 2011-246663 A [Patent Document 3] JP 2011-168053 A Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention has been made against the background of the problems of the conventional technology. That is, an object of the present invention is to provide an easily adhesive polyester film having excellent adhesion to a functional layer such as a hard coat layer or an adhesive. Another object of the present invention is to provide a laminated polyester film having the functional layer.

[0014] The present inventors have conducted extensive research to achieve the above object and have arrived at the present invention.

[0015] [1] An easily adhesive polyester film having a polyester film substrate and a coating layer on at least one side thereof, the coating layer being formed from a composition containing a polycarbonate polyurethane resin and a polyester resin, the polycarbonate polyurethane resin and the polyester resin both containing a cyclohexane ring in their respective molecules, and having a structure in which at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group. [2] The highly adhesive polyester film according to [1], wherein the polycarbonate polyurethane resin and the polyester resin each have a structure represented by formula (1) in their molecules. [ka] (In the formula, * indicates a binding site.) [3] The highly adhesive polyester film according to [2], wherein the structure represented by formula (1) is a structure represented by formula (2). [ka] (In the formula, * is the same as above.) [4] The highly adhesive polyester film according to [3], wherein the structure represented by formula (2) is a structure represented by formula (3). [ka] (In the formula, * is the same as above.) [5] The highly adhesive polyester film according to [4], wherein the structure represented by formula (3) is a structure derived from 1,4-cyclohexanedimethanol. [6] The highly adhesive polyester film according to any one of [1] to [5], wherein the content of the cyclohexane ring structure in the polycarbonate polyurethane resin is 5 to 55 mass %, and the content of the cyclohexane ring structure in the polyester resin is 5 to 20 mass %. [7] A laminated polyester film comprising a functional layer on a coating layer of the highly adhesive polyester film according to any one of [1] to [6]. Effect of the Invention

[0016] The highly adhesive polyester film of the present invention has excellent adhesion between the functional layer and the polyester film (especially adhesion after long-term storage, etc.) and has high adhesion reliability. It also has excellent blocking resistance and transparency. Therefore, it can be widely used in optical applications, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Polyester Film The polyester film used as a substrate in the easily adhesive polyester film of the present invention is a film mainly composed of polyester resin. Here, "a film mainly composed of polyester resin" means a film formed from a resin composition containing 50% by mass or more of polyester resin. When blended with other polymers (e.g., polycarbonate resin, polyimide resin, etc.), it means that the polyester resin is contained in an amount of 50% by mass or more, and when copolymerized with other monomers, it means that the polyester structural unit is contained in an amount of 50 mol% or more. Preferably, the polyester film contains 90% by mass or more of polyester resin, more preferably 95% by mass or more, and even more preferably 100% by mass.

[0018] The polyester resin material is not particularly limited, but a copolymer formed by polycondensation of a dicarboxylic acid component and a diol component, or a blend resin thereof can be used. Examples of dicarboxylic acid components constituting the polyester resin include terephthalic acid, isophthalic acid, orthophthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracenedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, and dodecadicarboxylic acid.

[0019] Examples of diol components constituting the polyester resin include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadiol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.

[0020] The dicarboxylic acid component and the diol component may each be used alone or in combination of two or more kinds. In addition, other polycarboxylic acid components such as trimellitic acid and other polyol components such as trimethylolpropane may be appropriately added.

[0021] Specific examples of polyester resins include polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, and among these, polyethylene terephthalate is preferred in terms of the balance between physical properties and cost. In addition, in order to control optical properties such as polarization, it is also a preferred embodiment to contain other copolymerization components or other polymers. From the viewpoint of controlling the optical properties of the polyester film, preferred copolymerization components include diethylene glycol and copolymerization components having norbornene in the side chain.

[0022] The intrinsic viscosity of the polyester resin (solvent: phenol / tetrachloroethane=60:40) is, for example, 0.50 to 1.0 dl / g.

[0023] In order to improve the handling properties of the polyester film, such as slipperiness and windability, inert particles can be contained in the film. Examples of inert particles include inorganic particles such as silica, kaolinite, talc, light calcium carbonate, heavy calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, zinc sulfate, zinc carbonate, titanium dioxide, satin white, aluminum silicate, diatomaceous earth, calcium silicate, aluminum hydroxide, hydrated halloysite, magnesium carbonate, and magnesium hydroxide. The average particle size of the inert particles can be, for example, 200 to 5000 nm, and further 250 to 4500 nm. This average particle size is measured using the method described in the Examples (average particle size based on number by SEM). In order to maintain high transparency, it is preferable that the content of inactive particles in the film is as small as possible. Therefore, it is preferable to have a multi-layer structure in which particles are contained only in the surface layer of the film, or to have the film substantially free of particles and to have fine particles contained only in the coating layer laminated on at least one side of the polyester film.

[0024] Incidentally, "substantially free of particles" means, for example, in the case of inorganic particles, that the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit when the elements derived from the particles are quantitatively analyzed by fluorescent X-ray analysis. This is because even if particles are not intentionally added to the base film, contaminants derived from foreign matter or dirt attached to the raw material resin or the line or equipment in the film manufacturing process may peel off and be inevitably mixed into the film.

[0025] In addition, when the polyester film is made into a multi-layer structure, it may be made into a two-kind three-layer structure in which the inner layer does not substantially contain inactive particles and only the outermost layer (second layer) contains inactive particles, which is preferable because it can achieve both transparency and processability.

[0026] The polyester film as the substrate may be a single layer or a laminate of two or more layers. In addition, various additives can be contained in the film as needed, as long as the effects of the present invention are achieved. Examples of additives include antioxidants, light resistance agents, gelation inhibitors, organic wetting agents, antistatic agents, ultraviolet absorbers, surfactants, etc. When the film has a laminated structure, it is also preferable to contain additives according to the function of each layer as needed. For example, it is also a preferred embodiment to add an ultraviolet absorber or the like to the inner layer in order to prevent photodegradation of the polarizer.

[0027] The polyester film can be produced according to a conventional method. For example, the polyester film can be obtained by melt-extruding a material containing the above-mentioned polyester resin into a film shape, and then cooling and solidifying the material on a casting drum to form a film. As the polyester film in the present invention, either a non-stretched film or a stretched film can be used, but a stretched film is preferable from the viewpoint of durability such as mechanical strength and chemical resistance.

[0028] When the polyester film is a stretched film, the stretching method is not particularly limited, and may be a longitudinal uniaxial stretching method, a transverse uniaxial stretching method, a longitudinal and transverse sequential biaxial stretching method, a longitudinal and transverse simultaneous biaxial stretching method, etc. When stretching a polyester film, the stretching may be performed before laminating an easily adhesive coating layer described later, or after laminating an easily adhesive coating layer. It is also possible to perform uniaxial stretching in the longitudinal or transverse direction before laminating an easily adhesive coating layer, and stretch in the other direction after laminating the coating layer.

[0029] Coating layer The adhesive polyester film of the present invention has an adhesive coating layer laminated on at least one surface of the polyester film as the substrate. The coating layer can be formed from a composition containing a binder resin and, if necessary, additives.

[0030] The composition of each coating layer will be described in detail below. The binder resin constituting the coating layer is a resin having high adhesion, and includes a polycarbonate polyurethane resin, which is a urethane resin having a polycarbonate structure, and a polyester resin. Each resin has a structure in which a cyclohexane ring is contained in the molecule, and at least one hydrogen atom on the cyclohexane ring is replaced with a hydrocarbon group. In other words, at least one hydrogen atom on the cyclohexane ring is bonded to a carbon atom of a hydrocarbon group (e.g., an alkyl group having 1 to 3 carbon atoms, an alkylene group having 1 to 3 carbon atoms, etc.). By adopting such a coating layer, the adhesion between the polyester film substrate and the functional layer is dramatically improved.

[0031] The reason for this is that the coating layer has a good compatibility with the composition of the functional layer described later. In addition, the functional layer is obtained by UV curing by UV irradiation and has a crosslinked network structure. Since the polycarbonate polyurethane resin and the polyester resin of the coating layer are both resins containing units having a cyclohexane ring, the resins interact with each other, making them more compatible and entangled. In addition, it is considered that the entangled resins are entangled with the network structure of the functional layer formed thereon, resulting in a coating layer with better adhesion than conventional coating layers. Furthermore, since the coating layer contains a polyester resin, it is considered that the adhesion to the polyester film, which is the substrate, is also improved, resulting in a coating layer with better adhesion.

[0032] Polycarbonate polyurethane resin and polyester resin have a structure in which at least one hydrogen atom on a cyclohexane ring is substituted with a hydrocarbon group, and an example of such a structure is a structure represented by formula (1). [ka] (In the formula, * indicates a binding site.) Here, * is a site that bonds to an atom that constitutes the resin. The atom may be the same or different and may be a hydrogen atom, a carbon atom, an oxygen atom, a nitrogen atom, etc. Of the two *, at least one is preferably a carbon atom, an oxygen atom, a nitrogen atom, etc.

[0033] As the structure represented by formula (1), a structure represented by formula (2) is preferred. [ka] (In the formula, * is the same as above.)

[0034] As the structure represented by formula (2), a structure represented by formula (3) is preferred. [ka] (In the formula, * is the same as above.)

[0035] The structure represented by the above formula (3) is more preferably a structure derived from cyclohexanedimethanol (particularly 1,4-cyclohexanedimethanol). In this case, the two * marks become the sites for bonding to oxygen atoms constituting the resin.

[0036] It is necessary for the polycarbonate polyurethane resin to have a structure in which the molecule contains a cyclohexane ring and at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group.

[0037] The content of the cyclohexane ring structure in the polycarbonate polyurethane resin is usually 5% by mass or more and 55% by mass or less, preferably 10% by mass or more and 50% by mass or less, and more preferably 15% by mass or more and 45% by mass or less. If the content is 5% by mass or more, there is a sufficient number of cyclohexane ring units that interact with each other between the resins, so that the strength of the resin in the coating layer is maintained and the adhesion is likely to be good under high temperature and high humidity conditions. If the content is 55% by mass or less, the flexibility of the resin in the coating layer is maintained and the adhesion is likely to be good under normal temperature and high temperature and high humidity conditions. The content of the cyclohexane ring structure in the polycarbonate polyurethane resin is the ratio of the cyclohexane ring structure (C6H 10 Specifically, it can be calculated from "the molecular weight and mole % of each component such as the polycarbonate diol component and the diisocyanate component constituting the polycarbonate polyurethane resin", "the mole % of the component having a cyclohexane ring", and "the molecular weight ratio of the cyclohexane ring structure to the molecular weight of the component having a cyclohexane ring".

[0038] Polycarbonate polyurethane resin is a product of an addition reaction of a polycarbonate diol component, a diisocyanate component, and, if necessary, a diol component as a chain extender, and at least one of these components contains a cyclohexane ring and has a structure in which at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group.

[0039] Examples of diol components necessary for preparing polycarbonate polyurethane resin include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,4-cyclohexanediethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadiol, 2,2-bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, etc. Among these, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, and 1,4-cyclohexanediethanol have a structure in which at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group, and are particularly preferred. In addition, these diol components can be used alone or in combination of two or more. The ratio of two or more to be combined is not particularly limited, and can be adjusted so as to obtain a polycarbonate polyurethane that has the required properties.

[0040] Examples of diisocyanate components necessary for preparing polycarbonate polyurethane resin include toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4-methylenebiscyclohexyl diisocyanate, 1,2-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, etc. Among these, isophorone diisocyanate, 4,4-methylenebiscyclohexyl diisocyanate, 1,2-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, etc. have a structure in which at least one hydrogen atom on the cyclohexane ring is replaced with a hydrocarbon group, and are particularly preferred. In addition, these isocyanate components can be used alone or in combination of two or more. The ratio when two or more are combined is not particularly limited, and can be adjusted so as to obtain a polycarbonate polyurethane having the required properties.

[0041] The polyester resin used in combination with the polycarbonate polyurethane resin also contains a cyclohexane ring in its molecule, and has a structure in which at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group.

[0042] The content of the cyclohexane ring structure in the polyester resin is usually more preferably 5% by mass or more and 20% by mass or less, and more preferably 10% by mass or more and 15% by mass or less. By making the content 20% by mass or less, it becomes easier to ensure the mobility and flexibility of the resin, and by making it 5% by mass or more, the number of units of the cyclohexane ring structure that interact with the polycarbonate polyurethane resin can be ensured, ensuring the strength of the resin in the coating layer and making it easier to maintain adhesion under high temperature and high humidity conditions. The content of the cyclohexane ring structure in the polyester resin is the number of cyclohexane ring structures (CH 10Specifically, it can be calculated from "the mole % and molecular weight of each monomer component constituting the polyester resin", "the mole % of the monomer component having a cyclohexane ring among all the monomer components", and "the proportion of the molecular weight of the cyclohexane ring structure among the molecular weight of the monomer component having a cyclohexane ring".

[0043] The polyester resin is a copolymer polyester consisting of a dicarboxylic acid component and a diol component, which is a polycondensation product of the dicarboxylic acid component and the diol component. The dicarboxylic acid component and the diol component may each be used alone or in combination of two or more. In the present invention, at least one of the dicarboxylic acid component and the diol component has a structure containing a cyclohexane ring and having at least one hydrogen atom on the cyclohexane ring substituted with a hydrocarbon group.

[0044] Examples of dicarboxylic acid components include terephthalic acid, isophthalic acid, orthophthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracenedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, cyclohexylmethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, cyclohexylmethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, dodecadicarboxylic acid, and 1,1-cyclohexanediacetic acid. Among these, cyclohexylmethylmalonic acid, cyclohexylmethylsuccinic acid, 1,1-cyclohexanediacetic acid, and the like are particularly preferred because they have the above-mentioned structure in which at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group.

[0045] If necessary, a small amount of a monocarboxylic acid such as cyclohexylacetic acid may be used.

[0046] Examples of the diol component include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,4-cyclohexanediethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadiol, 2,2-bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, etc. Among these, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 1,4-cyclohexanediethanol, etc., have a structure in which at least one hydrogen atom on the above-mentioned cyclohexane ring is substituted with a hydrocarbon group, and are particularly preferred.

[0047] If necessary, a monool such as cyclohexanemethanol may be used in a small amount.

[0048] The ratio of the dicarboxylic acid component and the diol component when combined is not particularly limited, and can be adjusted so as to obtain a polyester having the required properties.

[0049] The effects of the present invention are effectively achieved by the polycarbonate polyurethane resin and polyester resin used in the coating layer, both of which contain a cyclohexane ring and a structure in which at least one hydrogen atom on the cyclohexane ring is replaced with a hydrocarbon group. Although the exact mechanism by which the effects of the present invention are achieved is not clear, the coating layer of the present invention can improve the flexibility of the resin while maintaining the rigidity of the resin, and therefore functions best as a coating layer. In other words, not only is the coating layer excellent in adhesion to the substrate, such as the polyester film and the functional layer, but the adhesion over time is also greatly improved. This makes it possible to obtain a film that maintains its quality for a long period of time.

[0050] (Crosslinking agent) In the present invention, in order to form a crosslinked structure between resins in the coating layer, the composition used to form the coating layer may contain a crosslinking agent. By including a crosslinking agent, it becomes possible to further improve adhesion under high temperature and high humidity. Specific crosslinking agents include, for example, urea-based, epoxy-based, melamine-based, isocyanate-based, oxazoline-based, and carbodiimide-based crosslinking agents. Among these, isocyanate-based crosslinking agents are preferred from the viewpoint of the stability over time of the coating liquid and the effect of improving adhesion under high temperature and high humidity treatment. In addition, a catalyst or the like can be appropriately used as necessary to promote the crosslinking reaction.

[0051] When the coating layer forming composition contains a binder resin and a crosslinking agent, when the total mass of the binder resin and the crosslinking agent is taken as 100 mass%, the content of the binder resin is preferably 50 to 95 mass% from the viewpoint of adhesion, more preferably 55 to 90 mass%, even more preferably 60 to 90 mass%, and most preferably 80 to 90 mass%. If it is 95 mass% or less, the strength of the coating film of the coating layer is maintained and the adhesion is good under high temperature and high humidity, and if it is 50 mass% or more, the flexibility of the coating layer is maintained and the adhesion is maintained at room temperature and under high temperature and high humidity, which is preferable. In addition, when the total mass of the binder resin and the crosslinking agent is taken as 100 mass%, the content of the crosslinking agent is preferably 5 to 50 mass%, more preferably 10 to 45 mass%, even more preferably 10 to 40 mass%, and most preferably 10 to 20 mass%.

[0052] In the present invention, it is important that the binder resin contains a polycarbonate polyurethane resin and a polyester resin. The ratio of the two is not particularly limited as long as the physical properties of the resulting coating layer can be ensured, and when the total amount of the binder resin is taken as 100 mass%, the polycarbonate polyurethane resin is usually preferably 40 mass% or more and 85 mass% or less, more preferably 45 mass% or more and 80 mass% or less, and even more preferably 50 mass% or more and 75 mass% or less. By making the polycarbonate polyurethane resin 40 mass% or more, the balance between the flexibility and hardness of the urethane resin can be ensured, and the adhesion over time can be ensured. In addition, by making it 85 mass% or less, the balance between hardness and softness as a coating layer can be maintained and the flexibility can be improved, so that it functions best as a coating layer.

[0053] When using an isocyanate-based crosslinking agent as a crosslinking agent, it is preferable to use a blocking agent to control the reactivity of isocyanate. Examples of blocking agents include bisulfite-based compounds such as sodium bisulfite; pyrazole-based compounds such as 3,5-dimethylpyrazole, 3-methylpyrazole, 4-bromo-3,5-dimethylpyrazole, and 4-nitro-3,5-dimethylpyrazole; phenol-based compounds such as phenol and cresol; aliphatic alcohol-based compounds such as methanol and ethanol; active methylene-based compounds such as dimethyl malonate and acetylacetone; mercaptan-based compounds such as butyl mercaptan and dodecyl mercaptan; acid amide-based compounds such as acetanilide and acetic acid amide; lactam-based compounds such as ε-caprolactam and δ-valerolactam; acid imide-based compounds such as succinimide and maleimide; oxime-based compounds such as acetaldoxime, acetoneoxime, and methylethylketoxime; and amine-based compounds such as diphenylaniline, aniline, and ethyleneimine. From the viewpoint of reactivity, a blocking agent having a pyrazole skeleton is suitable for this system.

[0054] It is preferable to introduce a hydrophilic group into the blocked isocyanate crosslinking agent from the viewpoint of imparting water dispersibility in an aqueous solvent. As the hydrophilic group, an anionic group such as a carboxyl group or a sulfonic acid group, or a nonionic group such as an oxyalkyl group is preferable. These crosslinking agents having a hydrophilic group can be prepared by reacting in advance a polyisocyanate, which is the base of the blocked isocyanate, with a compound having a hydrophilic group and a reactive group such as a hydroxyl group.

[0055] (Additives) In the coating layer of the present invention, known additives such as surfactants, antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic particles, antistatic agents, nucleating agents, etc. may be added within the range that does not impair the effects of the present invention. However, it is preferable not to use substances that are undesirable from the environmental standpoint, etc.

[0056] In order to further improve the blocking resistance of the coating layer, it is also a preferred embodiment to add inactive particles to the coating layer. Examples of particles to be contained in the coating layer include inorganic particles and organic polymer particles. Examples of inorganic particles include titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, or mixtures thereof, and further, other general inorganic particles such as calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, calcium fluoride, etc. can also be used in combination. Examples of organic polymer particles include polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based.

[0057] The average particle size of the inactive particles in the coating layer (average particle size based on the number of particles measured by SEM; the same applies below) is preferably 0.04 to 2.0 μm, more preferably 0.1 to 1.0 μm. When the average particle size of the inactive particles is 0.04 μm or more, it is easy to form irregularities on the surface of the coating layer, which improves the handling properties such as the slipperiness and winding properties of the highly adhesive polyester film, and the processability during lamination is good, which is preferable. On the other hand, when the average particle size of the inactive particles is 2.0 μm or less, it is preferable that the particles are less likely to fall off. The particle concentration in the coating layer is preferably 1 to 20 mass% based on the resin content.

[0058] (Formation of coating layer) A coating layer forming composition (hereinafter also referred to as "coating liquid") for forming a coating layer may further contain a surfactant for the purpose of improving leveling during application and degassing the coating liquid. Examples of the surfactant include cationic, anionic, and nonionic surfactants, and silicone, acetylene glycol, and fluorine-based surfactants are preferred. These surfactants are preferably contained in the coating layer forming composition within a range that does not impair the effect of suppressing iridescent color under a three-wavelength LED light source or the adhesion.

[0059] As a method for applying the coating liquid onto the polyester film, either a so-called in-line coating method in which the coating is performed simultaneously with the polyester film formation, or a so-called off-line coating method in which the coating is performed using a separate coater after the polyester base film is formed can be used, but the in-line coating method is more efficient and more preferred.

[0060] Regarding the coating method, any known method can be used for applying the coating liquid to a polyethylene terephthalate (hereinafter abbreviated as PET) film. For example, reverse roll coating, gravure coating, kiss coating, die coater, roll brush, spray coating, air knife coating, wire bar coating, pipe doctor, impregnation coating, curtain coating, etc. can be mentioned. These methods can be used alone or in combination for coating.

[0061] In the present invention, the method of providing a coating layer on a polyester film includes a method of coating a coating liquid containing a solvent, particles, and a resin on a polyester film and drying the coating liquid. The solvent includes water or a mixture of water and an organic solvent, but from the viewpoint of environmental issues, it is preferable to use water alone or a mixture of water and a water-soluble organic solvent. For example, examples of water-soluble organic solvents include alcohol-based solvents such as isopropyl alcohol and ethanol; ketone-based solvents such as methyl ethyl ketone; ether-based solvents such as butyl cellosolve; amine-based solvents such as triethanolamine; and amide-based solvents such as N-methylpyrrolidone.

[0062] The solid content of the coating liquid is preferably 2% by mass or more, more preferably 4% by mass or more, based on the total mass of the coating liquid, depending on the type of binder resin, the type of solvent, etc. The solid content of the coating liquid is preferably 35% by mass or less, more preferably 15% by mass or less.

[0063] The drying temperature after coating also depends on the type of binder resin, the type of solvent, the presence or absence of a crosslinking agent, the solids concentration, etc., but is preferably 80° C. or higher and 250° C. or lower.

[0064] The amount of the coating solution applied is, for example, 0.03 to 0.24 g / m2 in terms of the solid content on the polyester film after drying. 2 , and 0.06 to 0.18 g / m 2 In the case where a film stretching step is carried out after coating and drying, the solid content on the polyester film after stretching can be adjusted so as to be within the above range.

[0065] The stretching step may be either uniaxial stretching or biaxial stretching. The stretched polyester film may be heat-treated (for example, at 70 to 250°C, preferably 80 to 245°C) while being fixed by a tenter, and may further be relaxed at 120 to 250°C.

[0066] As described above, the highly adhesive polyester film of the present invention is produced through the coating, drying, stretching and heat treatment steps.

[0067] The thickness of the coating layer is 30 nm or more and 200 nm or less. If it is prepared within this range, it is preferable because it is easy to achieve both processability and adhesion. More preferably, it is 50 nm or more and 150 nm or less, and even more preferably, it is 70 nm or more and 100 nm or less. If the thickness of the coating layer is 30 nm or more, it is preferable because the adhesion is good. If the thickness of the coating layer is 200 nm or less, it is preferable because blocking is unlikely to occur.

[0068] The thickness of the coating layer was determined by observing the cross section of the cut film with a transmission electron microscope (TEM) and measuring the thickness of the coating layer at 10 random points, and averaging the measured thickness.

[0069] Laminated Polyester Film The present invention also provides a laminated polyester film in which a functional layer having various properties is provided on a coating layer of an easily adhesive polyester film. The functional layer refers to a layer having functionality such as a hard coat layer, an antiglare layer, an antiglare antireflection layer, an antireflection layer, a low reflection layer, an antistatic layer, etc., for the purpose of preventing reflection, suppressing glare, suppressing rainbow unevenness, suppressing scratches, etc. Various functional layers known in the technical field can be used, and the type is not particularly limited.

[0070] For example, when a hard coat layer is formed on a coating layer, a known material for the hard coat layer can be used, and is not particularly limited. As the material, a resin compound (particularly a curable resin) that polymerizes and / or reacts by drying, heat, chemical reaction, or by irradiating with any of an electron beam, radiation, and ultraviolet light can be used. Examples of such curable resins include melamine-based, acrylic-based, silicone-based, and polyvinyl alcohol-based curable resins, but photocurable acrylic-based curable resins are preferred in terms of obtaining high surface hardness or optical design. As such an acrylic-based curable resin, a multifunctional (meth)acrylate-based monomer or an acrylate-based oligomer can be used, and examples of the acrylate-based oligomer include polyester acrylate-based, epoxy acrylate-based, urethane acrylate-based, polyether acrylate-based, polybutadiene acrylate-based, and silicone acrylate-based. By mixing a reactive diluent, a photopolymerization initiator, a sensitizer, and the like with these acrylic-based curable resins, a coating composition for forming the optical functional layer can be obtained.

[0071] The hard coat layer may have an anti-glare function that scatters external light. The anti-glare function is obtained by forming irregularities on the surface of the hard coat layer. In this case, the haze of the film is ideally 0 to 50%, more preferably 0 to 40%, and particularly preferably 0 to 30%. Of course, 0% is ideal, and it may be 0.2% or more, or 0.5% or more.

[0072] In addition, a layer having a different refractive index may be provided as a functional layer to change the light transmission characteristics and suppress the reflection of light, thereby performing low reflection processing (anti-reflection processing). The refractive index of a functional layer such as a hard coat layer is preferably adjusted to have a reflectance of 0 to 1.0%, more preferably 0 to 0.8%, and particularly preferably 0 to 0.5%. Of course, 0% is ideal, and it may be 0.05% or more, or 0.1% or more.

[0073] The easily adhesive polyester film of the present invention can be used as a polarizer protective film. In general, a polarizing plate is formed by disposing a polarizer protective film on both sides of a polarizer, and it is preferable that the polarizer protective film on at least one side of the polarizer is the easily adhesive polyester film of the present invention. The polarizer protective film on the other side may be the easily adhesive polyester film of the present invention, or may be a film without birefringence, such as a triacetyl cellulose film, an acrylic film, or a norbornene-based film.

[0074] Examples of polarizers include a polyvinyl alcohol-based film containing a dichroic material such as iodine. The polarizer protective film is attached to the polarizer directly or via an adhesive layer, and from the viewpoint of improving adhesion, it is preferable to attach it via an adhesive. In this case, it is preferable to arrange the coating layer of the highly adhesive polyester film of the present invention on the polarizer surface or the adhesive layer surface. Examples of polarizers that are preferable for attaching the polyester film of the present invention include polarizers obtained by dyeing and adsorbing iodine or a dichroic material to a polyvinyl alcohol-based film, uniaxially stretching the film in an aqueous boric acid solution, and washing and drying the film while maintaining the stretched state. The stretching ratio of the uniaxial stretching is usually about 4 to 8 times. As the polyvinyl alcohol-based film, polyvinyl alcohol is suitable, and commercially available products such as "Kuraray Vinylon" [manufactured by Kuraray Co., Ltd.], "Tohcello Vinylon" [manufactured by Tohcello Co., Ltd.], and "Nippon Vinylon" [manufactured by Nippon Synthetic Chemical Industry Co., Ltd.] can be used. The dichroic material includes iodine, disazo compounds, polymethine dyes, and the like.

[0075] When the adhesive layer is to be thinned, the adhesive to be applied to the polarizer is preferably water-based, that is, the adhesive component is dissolved or dispersed in water. For example, a composition using a polyvinyl alcohol resin, a urethane resin, or the like as a main component and, if necessary, blending an isocyanate compound, an epoxy compound, or the like, can be used to improve adhesion. The thickness of the adhesive layer is preferably 5 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less.

[0076] When a polyvinyl alcohol resin is used as the main component of the adhesive, modified polyvinyl alcohol resins such as partially saponified polyvinyl alcohol, fully saponified polyvinyl alcohol, carboxyl group-modified polyvinyl alcohol, acetoacetyl group-modified polyvinyl alcohol, methylol group-modified polyvinyl alcohol, and amino group-modified polyvinyl alcohol may be used. The concentration of the polyvinyl alcohol resin in the adhesive is preferably 1 to 10% by mass, and more preferably 2 to 7% by mass.

[0077] When it is desired to further increase productivity, it is preferable to use a photocurable adhesive as the adhesive to be applied to the polarizer. The thickness of the adhesive layer after curing can be set arbitrarily by designing the properties of the polarizing plate, and it is preferable that it is small from the viewpoint of reducing the adhesive material cost. In general, it is 0.01 to 20 μm, preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm. When the thickness of the adhesive layer is 0.01 μm or more, air bubbles are unlikely to be mixed into the adhesive layer, and the adhesiveness and durability are good, which is preferable. When the adhesive layer is 20 μm or less, the reaction rate of the adhesive is sufficient, and the wet heat resistance of the polarizing plate is good, which is preferable.

[0078] The photocurable adhesive preferably contains as a main component an epoxy compound containing no aromatic ring, a photocationically curable component (I), and a photocationic polymerization initiator (II).

[0079] The photocationically curable component (I) is preferably mainly composed of an epoxy compound that does not contain an aromatic ring. The epoxy compound that does not contain an aromatic ring is an epoxy compound other than an aromatic epoxy compound, and is hereinafter referred to as an aliphatic epoxy compound. An "epoxy compound" is a compound having at least one epoxy group in the molecule. The aliphatic epoxy compound that is the main component may contain two or more epoxy compounds. The "main component" means that the content of the aliphatic epoxy compound is 50% by mass or more in 100% by mass of the photocurable adhesive. The content of the aliphatic epoxy compound is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more.

[0080] The aliphatic epoxy compound may be an epoxy compound having an alicyclic ring, or may be an epoxy compound not containing an alicyclic ring and consisting only of a linear hydrocarbon structure and / or a branched hydrocarbon structure. The aliphatic epoxy compound may contain an unsaturated bond such as a double bond, and may further contain a heteroatom (oxygen atom, nitrogen atom, sulfur atom, halogen atom, etc.) other than the oxygen atom contained in the epoxy group.

[0081] The photocationic polymerization initiator (II) can initiate cationic polymerization by irradiation with active energy rays, and cure the photocationic curable component (I) to form an adhesive layer. The photocationic polymerization initiator (II) generates cationic species or Lewis acids by irradiation with active energy rays such as visible light, ultraviolet light, X-rays, and electron beams, and initiates the polymerization reaction of the photocationic curable component. The photocationic polymerization initiator (II) acts catalytically when exposed to light, and therefore has excellent storage stability and workability even when mixed with the photocationic curable component.

[0082] Examples of the photocationic polymerization initiator (II) include aromatic diazonium salts; onium salts such as aromatic iodonium salts and aromatic sulfonium salts; and iron-arene complexes.

[0083] Examples of aromatic diazonium salts include benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, and benzenediazonium hexafluoroborate.

[0084] Examples of aromatic iodonium salts include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate.

[0085] Examples of aromatic sulfonium salts include triphenylsulfonium hexafluorophosphate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4,4-bis[diphenylsulfonio]diphenyl sulfide bishexafluorophosphate, 4,4-bis[di(β-hydroxyethoxy)phenylsulfonio]diphenyl sulfide bishexafluoroantimonate, 4,4-bis[di(β-hydroxyethoxy)phenylsulfonio]diphenyl sulfide bishexafluorophosphate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone hexafluoroantimonate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate, and 4-phenylcarbonyl-4-diphenylsulfonio-diphenyl sulfide. hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4-diphenylsulfonio-diphenylsulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4-di(p-toluyl)sulfonio-diphenylsulfide tetrakis(pentafluorophenyl)borate.

[0086] Examples of iron-arene complexes include xylene-cyclopentadienyliron(II) hexafluoroantimonate, cumene-cyclopentadienyliron(II) hexafluorophosphate, and xylene-cyclopentadienyliron(II) tris(trifluoromethylsulfonyl)methanide.

[0087] The photocationic polymerization initiator (II) may be used alone or in combination of two or more. Among the above, aromatic sulfonium salts are preferably used because they have ultraviolet absorption properties even in the wavelength region around 300 nm, and therefore can provide an adhesive layer having excellent curing properties and good mechanical strength and adhesive strength.

[0088] The content of the photocationic polymerization initiator (II) is preferably 1 to 10 parts by mass, more preferably 2 to 6 parts by mass, based on 100 parts by mass of the total photocationic curable component (I). By including 1 part by mass or more of the photocationic polymerization initiator (II), the photocationic curable component (I) can be sufficiently cured, and the obtained polarizing plate can be given high mechanical strength and adhesive strength. On the other hand, if the content is high, the ionic substance in the cured product increases, which increases the hygroscopicity of the cured product and may reduce the durability of the polarizing plate. Therefore, the content of the photocationic polymerization initiator (II) is preferably 10 parts by mass or less based on 100 parts by mass of the photocationic curable component (I).

[0089] The laminated polyester film of the present invention is mainly used for optical films in general, and examples of the film include prism lens sheets, AR (anti-reflection) films, hard coat films, diffusion plates, shatter-proof films, and other base films for optical members of LCDs, flat TVs, CRTs, and other displays, near-infrared absorbing filters that are members for front panels of plasma displays, and transparent conductive films for touch panels and electroluminescence displays, etc. The film can be suitably used for any of these applications.

[0090] Examples of the acrylic resin that is cured by electron beams or ultraviolet rays for forming the above-mentioned functional layer include a composition containing a (meth)acrylate oligomer, which is a reactive oligomer, and a (meth)acrylate-based monomer, which is a reactive monomer (reactive diluent). Examples of (meth)acrylate oligomers include compounds in which a reactive (meth)acrylic group is bonded to a (meth)acrylic resin skeleton, polyester acrylate, epoxy acrylate, polyurethane acrylate, silicone acrylate, melamine acrylate, and polyether acrylate. Examples of (meth)acrylate monomers include monofunctional monomers such as ethyl (meth)acrylate and ethylhexyl (meth)acrylate; and polyfunctional monomers such as trimethylolpropane tri(meth)acrylate, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate. If necessary, a third component can be appropriately added, for example, a relatively low molecular weight polyester resin, polyether resin, acrylic resin, epoxy resin, urethane resin, alkyd resin, spiroacetal resin, polybutadiene resin, polythiolpolyene resin, polyhydric alcohol, etc. can be contained.

[0091] In the case of electron beam or ultraviolet ray curing acrylic resin, for example, acetophenones, benzophenones, Michler's benzoyl benzoate, α-amyloxime ester, tetramethylthiuranium monosulfide, thioxanthones can be used as photopolymerization initiators in the above-mentioned resin. Also, a mixture of the photopolymerization initiator and a photosensitizer such as n-butylamine, triethylamine, tri-n-butylphosphine, etc. can be used.

[0092] Silicone-based (siloxane-based) thermosetting resins can be produced by hydrolysis and condensation reaction of one or more organosilane compounds in the presence of an acid or base catalyst. In particular, for low reflection applications, it is more effective to mix one or more fluorosilane compounds and carry out hydrolysis and condensation reaction in order to improve low refractive index, contamination resistance, etc.

[0093] Manufacturing of laminated polyester film The laminated polyester film of the present invention can be produced by providing a functional layer on the coating layer of the highly adhesive polyester film. Specific embodiments are described below, but the present invention is not limited thereto.

[0094] A functional layer forming composition (functional layer forming coating liquid) is applied to the coating layer surface of the above-mentioned easy-adhesive polyester film. Examples of the functional layer forming composition include the above-mentioned electron beam or ultraviolet curable acrylic resin (including its oligomer, monomer, etc.) or siloxane-based thermosetting resin. When the coating layer is provided on both sides of the easy-adhesive polyester film, it can be applied to at least one of the coating layer surfaces. The functional layer forming coating liquid does not need to be diluted in particular, but there is no particular problem if it is diluted with an organic solvent as required for its viscosity, wettability, coating thickness, etc. The coating film after the functional layer forming coating liquid is applied to the film can be dried as necessary, and then cured by irradiation with electron beams or ultraviolet rays and heating according to the curing conditions to form a functional layer.

[0095] More typically, the functional layer forming coating solution having the above composition is applied onto the coating layer of the highly adhesive polyester film using a wire bar or the like, and the solvent can be removed by drying, for example, at 60 to 100° C. for 0.5 to 10 minutes. Next, the film coated with the functional layer is irradiated with 250 to 600 mJ / cm 2 using, for example, a high-pressure mercury lamp. 2 By irradiating the film with ultraviolet light, a laminated polyester film having a functional layer can be obtained.

[0096] In the present invention, the thickness of the functional layer is preferably 1 to 15 μm. When the thickness of the functional layer is 1 μm or more, the effects of the functional layer on chemical resistance, scratch resistance, antifouling, etc. are efficiently exhibited, which is preferable. On the other hand, when the thickness is 15 μm or less, the flexibility of the functional layer is maintained, and there is no risk of cracks, etc. occurring, which is preferable.

[0097] The easily adhesive polyester film and laminated polyester film of the present invention are preferably highly transparent because they can be used mainly for optical applications. The lower limit of the haze is ideally 0%, and the closer to 0%, the more preferable. The upper limit of the haze is preferably 2%. If the haze is 2% or less, the light transmittance is good, and a clear image can be obtained in a liquid crystal display device, which is preferable. The haze can be measured, for example, according to the method described in the examples below.

[0098] (Evaluation of Adhesion) The adhesion between the polyester film and the functional layer in the laminated polyester film can be evaluated by the method described in the examples. Specifically, a laminated polyester film was prepared by forming a functional layer on the coating layer of an easily adhesive polyester film, and the adhesion X (%) was evaluated. Separately, after storing the easily adhesive polyester film for a long period of time, a laminated polyester film was prepared by forming a functional layer on the coating layer, and the adhesion Y (%) was evaluated. For long-term storage conditions, ideally the sample should be left in a room temperature environment for several weeks to several months, as is the case for normal storage, before measurement. However, since leaving the sample at room temperature takes an extremely long period of time, in this specification, as an alternative measurement method, accelerated conditions are used in which the sample is left in a high temperature and high humidity environment of 80°C and 90% RH for 24 hours, and then left at room temperature (10 to 30°C) for 12 hours. As is clear from Table 3 of the Examples, the adhesion X is usually 95% or more, more preferably 98% or more, and particularly 100%. When the adhesion X is 95% or more, it can be said that the adhesion between the coating layer and the functional layer is sufficiently maintained. Furthermore, the adhesion Y after long-term storage is usually 95% or more, more preferably 98% or more, and particularly 100%. When the adhesion Y is 95% or more, it can be said that the adhesion between the coating layer and the functional layer is sufficiently maintained even after long-term storage. In the highly adhesive polyester film of the present invention, both adhesion X and adhesion Y are high, and adhesion Y is equal to or hardly changes with respect to adhesion X.

[0099] Thus, the highly adhesive polyester film of the present invention has a feature that it has high adhesion reliability with the functional layer, and has high adhesion not only after film formation but also after exposure to a high temperature and high humidity environment (even after long-term storage). In other words, it has a feature that the adhesion X after film formation is sufficiently high, and the adhesion Y after long-term storage is also high. In other words, the above-mentioned X (%) and Y (%) satisfy the following formula (1). XY(%) ≦ 5...Equation (1)

[0100] The value of formula (1) is usually 5% or less, more preferably 3% or less, and particularly 0%. If it is 5% or less, it can be determined that there is no significant difference between the adhesion after film formation and the adhesion after wet heat treatment, and both are sufficiently adhered. Therefore, even if stored for a long time, there is no decrease in the adhesion of the functional layer, and it can be determined that adhesion reliability can be ensured.

[0101] In the present invention, "after film formation" refers to a state after a coating layer is formed on a polyester film (film formation), and refers to a state in which the polyester film is stored in a temperature environment of 40° C. or less for a period of 6 months or less after film formation. Within that period, the performance of the coating layer of the highly adhesive polyester film hardly changes.

[0102] Separately, the highly adhesive polyester film after film formation was wound into a roll as an actual product and left for 6 months in an environment of temperature: 0°C to 30°C and humidity: 10% RH to 80% RH. After that, a sample was taken from the roll, a functional layer was formed on the coating layer, and the adhesion Z (%) was evaluated. As is clear from Table 3 of the Examples, the adhesion Z is usually 90% or more, more preferably 95% or more, and particularly 100%. When the adhesion Z is 90% or more, it means that the adhesion Z of the highly adhesive polyester film is maintained and has high adhesion reliability even after being wound into a roll and left for a long period of time. EXAMPLES

[0103] The present invention will now be described in detail with reference to examples, comparative examples, and reference examples, but the present invention is not limited to the following examples. The measurement methods for the values ​​used in the present invention are as follows.

[0104] (1) Average particle size [Measurement method using a scanning electron microscope] The average particle size of particles present in the coating layer in the present invention can be measured by the following method: Particles are photographed with a scanning electron microscope (SEM), and the maximum diameters (the distance between the two most distant points) of 300 to 500 particles are measured at a magnification such that the size of the smallest particle is 2 to 5 mm, and the arithmetic average of these is taken as the average particle size.

[0105] [Dynamic Light Scattering Method] The average particle size of particles can also be determined by dynamic light scattering during the production of particles or films. The sol is diluted with a dispersion medium, and the average particle size is obtained by measuring with a submicron particle analyzer N4 PLUS (manufactured by Beckman Coulter) using the parameters of the dispersion medium, and calculating the average particle size using the cumulant method. In the dynamic light scattering method, the average particle size of the particles in the sol is observed, and when there is aggregation of particles, the average particle size of the aggregated particles is observed.

[0106] (2) Refractive index of particles The refractive index of the particles can be measured by the following method. After drying the inorganic particles at 150°C and grinding them in a mortar, the fine particles are immersed in solvent 1 (having a lower refractive index than the particles), and then solvent 2 (having a higher refractive index than the particles) is added little by little until the fine particles become almost transparent. The refractive index of this liquid is measured using an Abbe refractometer (Abbe refractometer manufactured by Atago Co., Ltd.). The measurement was performed at 23°C and with D-line (wavelength 589 nm). Solvents 1 and 2 are selected to be mutually miscible, and examples of the solvents that can be used depending on the refractive index include 1,1,1,3,3,3-hexafluoro-2-propanol, 2-propanol, chloroform, carbon tetrachloride, toluene, glycerin, and the like.

[0107] (3) Haze of optical adhesive polyester film The haze of the highly adhesive polyester film was measured in accordance with JIS K 7136:2000 using a turbidity meter (manufactured by Nippon Denshoku Co., Ltd., NDH2000).

[0108] (4) Adhesion of functional layer (1) A hard coat layer was formed on the easy-adhesive coating layer of the polyester film obtained in the example. The adhesion between the hard coat layer and the substrate film of the easy-adhesive polyester film on which the hard coat layer was formed was measured according to the description of 8.5.1 of JIS-K5400-1990.

[0109] The coating solution used for forming the hard coat layer was prepared as follows. (Preparation of Coating Solution L for Forming Hard Coat Layer) Methyl ethyl ketone 36.00% by mass Toluene 18.00% by mass Cyclohexanone 6.00% by mass Urethane acrylate 40.00% by mass (BS577 manufactured by Arakawa Chemical) Surfactant: 0.10% by mass Photopolymerization initiator 2.00% by mass (Omnirad184 manufactured by IGM Resins BV)

[0110] (Preparation of Coating Solution M for Forming Hard Coat Layer) Methyl ethyl ketone 64.40% by mass Dipentaerythritol hexaacrylate 27.20% by mass (Shin Nakamura Chemical A-DPH) Polyethylene glycol diacrylate 3.40% by mass (Kyoeisha Chemical Light Acrylate 9EG-A) Bisphenol A diacrylate 4.00% by mass (Kyoeisha Chemical Light Acrylate BP-4PA) Photopolymerization initiator 1.00% by mass (Omnirad184 manufactured by IGM Resins BV)

[0111] (Formation of hard coat layer) The highly adhesive polyester film produced in the examples was stored at a temperature and humidity of 20°C and 65% RH, and 12 hours after film formation, the coating solution for forming a hard coat layer (L or M) having the above composition was applied onto the highly adhesive coating layer using a #14 wire bar, and dried at 70°C for 1 minute to remove the solvent. Next, the film coated with the hard coat layer was irradiated with 300 mJ / cm using a high-pressure mercury lamp. 2 The hard coat film was irradiated with ultraviolet light of 1000 ohms to obtain a hard coat film having a hard coat layer with a thickness of 7 μm.

[0112] The specific method for measuring the adhesion is as follows. Using a cutter guide with a gap of 2 mm, 100 grid-shaped cuts were made on the hard coat layer surface, penetrating the hard coat layer and reaching the base film. Next, cellophane adhesive tape (manufactured by Nichiban, No. 405; 24 mm wide) was attached to the grid-shaped cut surface, and rubbed with an eraser to completely adhere it. Thereafter, the cellophane adhesive tape was peeled vertically from the hard coat layer surface of the easy-adhesive polyester film on which the hard coat layer was formed, and the number of squares peeled off from the hard coat layer surface was counted visually, and the adhesion between the hard coat layer and the base film was calculated from the following formula. Note that the squares that were partially peeled off were also counted as peeled squares. Adhesion (%) = {1-(number of peeled squares / 100)} x 100

[0113] (5) Adhesion of functional layer (2) A photocurable adhesive layer was formed on the easy-adhesive coating layer of the polyester film obtained in the example. The adhesion between the photocurable adhesive layer and the substrate film of the easy-adhesive polyester film on which the photocurable adhesive layer was formed was measured in accordance with the description of 8.5.1 of JIS-K5400-1990.

[0114] The coating liquid used for forming the photocurable adhesive layer was prepared as follows. (Preparation of Coating Solution N for Forming Photocurable Adhesive Layer) 3,4-epoxycyclohexylmethyl-3,4'-epoxycyclohexanecarboxylate 23.81% by mass (Daicel Celloxide2021P) 1,4-Cyclohexanedimethanol diglycidyl ether 23.81% by mass (Nagase ChemteX EX-216L) 3-Ethyl-3-[(3-ethyloxetan-3-yl)methoxymethyl]oxetane 47.62% by mass (Aronoxetane DOX221 manufactured by Toagosei) Cationic initiator 4.76% by weight (Sanapro CPI-100P) The aromatic component content in the total resin in the prepared photocurable adhesive layer-forming coating solution N was 13.3% in terms of molar ratio.

[0115] (Formation of photocurable adhesive layer) The adhesive polyester film produced in the examples described below was stored at a temperature and humidity of 20°C and 65% RH, and 12 hours after film formation, the adhesive coating layer was coated with the above-mentioned coating solution N for forming a photocurable adhesive layer using a #3 wire bar. Next, the film coated with the photocurable adhesive layer was irradiated with 500 mJ / cm using a high-pressure mercury lamp. 2 The film was irradiated with ultraviolet light of 1000 ohms to obtain a polarizer protective film having a photocurable adhesive layer with a thickness of 5 μm.

[0116] The specific method for measuring the adhesion is as follows. Using a cutter guide with a gap of 2 mm, 100 grid-shaped cuts were made on the surface of the photocurable adhesive layer, penetrating the photocurable adhesive layer and reaching the base film. Next, cellophane adhesive tape (manufactured by Nichiban, No. 405; 24 mm wide) was attached to the grid-shaped cut surface and rubbed with an eraser to completely adhere it. Thereafter, the cellophane adhesive tape was peeled vertically from the photocurable adhesive layer surface of the easy-adhesion polyester film on which the photocurable adhesive layer was formed, and the number of squares peeled off from the photocurable adhesive layer surface was visually counted, and the adhesion between the photocurable adhesive layer and the base film was calculated from the following formula. Note that the squares that were partially peeled off were also counted as peeled squares. Adhesion (%) = {1-(number of peeled squares / 100)} x 100

[0117] (6) Moisture and heat resistance (adhesion after exposure at 80℃ and 90% RH) The obtained adhesive polyester film was left in a high-temperature and high-humidity chamber at 80°C and 90% RH for 24 hours, and then left at room temperature (20°C and 65% RH) for 12 hours. After that, a functional layer was formed in the same manner as above, and the adhesion to the substrate film was measured.

[0118] (7) Reduced viscosity ηsp / c (unit: dl / g) 0.10 g of the polyester resin was dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4), and the viscosity was measured at 30° C. using an Ubbelohde viscosity tube.

[0119] (8) Cross-sectional observation using a transmission electron microscope The obtained adhesive polyester film was cut into 1 mm x 10 mm pieces and embedded in epoxy resin, and then a cross-sectional thin section parallel to the short side of the embedded sample piece was prepared using an ultramicrotome. The thin section was then stained with ruthenium tetroxide, and a portion of the thin section that was not significantly damaged was observed using a transmission electron microscope (JEM2100 manufactured by JEOL Ltd.) at an acceleration voltage of 200 kV and a magnification of 20,000 times. From the observed images of the coating layer, the thickness of the coating layer was measured at 10 points for each level, and the average value was taken as the thickness of the coating layer.

[0120] (9) Polyester resin composition The polyester resin was dissolved in deuterated chloroform, and the results were analyzed using a Varian Gemini-200 nuclear magnetic resonance analyzer (NMR). 1 H-NMR analysis was carried out to determine the molar percentage of each component from the integral ratio.

[0121] (10) Viscosity of Polyester Resin Dispersion The polyester resin aqueous dispersion was placed in a 140 cc glass bottle, and the viscosity was measured for 1 minute at a rotation speed of 60 rpm using a No. 1 or No. 2 rotor of a viscometer model BL (TOKIMEC INC.) in a thermostatic bath at 25° C. The viscosity of the polyester resin aqueous dispersion was measured.

[0122] [Polyurethane resin] Synthesis of polyurethane resin (PCPU-1): In a four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer, 29.4 parts by mass of dicyclohexylmethane-4,4'-diisocyanate, 63.6 parts by mass of polycarbonate diol with a melting point of 33 ° C., mainly made of 1,4-butanediol / 1,6-hexanediol (= 80 / 20 (molar ratio)) with a number average molecular weight of 1000, 7 parts by mass of dimethylolpropionic acid, and 200 parts by mass of ethyl methyl ketone as a solvent were added, and stirred for 3 hours at 75 ° C. under a nitrogen atmosphere. The infrared spectrum of the reaction solution was measured, and the disappearance of the isocyanate group in the reaction solution was confirmed. Next, after cooling the solution to room temperature, 8.2 parts by mass of triethylamine was added to obtain a polyurethane resin (PCPU-1) solution with a solid content of 50.0% by mass. The proportion (content) of cyclohexane ring structures in the entire polycarbonate polyurethane (PCPU-1) was 10.7% by mass.

[0123] Preparation of water dispersion (PCPU-1WD) of polyurethane resin (PCPU-1): A specified amount of water was added to a reaction vessel equipped with a homodisperser capable of high speed stirring, and the temperature was adjusted to 25°C. The mixture was then stirred for 2000 min. -1 While stirring and mixing at 100°C, the polyurethane resin (PCPU-1) solution was gradually added to disperse in water. The solvent, ethyl methyl ketone, was then removed under reduced pressure. The concentration was adjusted with water to prepare a water dispersion (PCPU-1WD) of polycarbonate polyurethane resin (PCPU-1) with a solid content of 35.0% by mass.

[0124] Synthesis of polyurethane resin (PCPU-2) and preparation of water dispersion (PCPU-2WD): Except for changing the main raw material of polycarbonate diol to 1,4-cyclohexanedimethanol / 1,6-hexanediol (=75 / 25 (molar ratio)), (PCPU-2) was prepared in the same manner as the synthesis of (PCPU-1) above, and an aqueous dispersion (PCPU-2WD) was obtained in the same manner as the preparation of (PCPU-1WD). The proportion (content) of the cyclohexane ring structure in the entire polycarbonate polyurethane (PCPU-2) was 39.4 mass%.

[0125] Synthesis of polyurethane resin (PCPU-3) and preparation of water dispersion (PCPU-3WD): Instead of dicyclohexylmethane-4,4'-diisocyanate, cyclohexane-1,2-diylbis(methylene)diisocyanate was used, and the molar number was adjusted. Except for this, (PCPU-3) was prepared in the same manner as in the synthesis of (PCPU-1) above, and a water dispersion (PCPU-3WD) was obtained in the same manner as in the preparation of (PCPU-1WD). The proportion (content) of the cyclohexane ring structure in the entire polycarbonate polyurethane (PCPU-3) was 11.5% by mass.

[0126] Synthesis of polyurethane resin (PCPU-4) and preparation of water dispersion (PCPU-4WD): Except for changing the main raw material of polycarbonate diol to 1,4-cyclohexanedimethanol / 1,6-hexanediol (=75 / 25 (molar ratio)), (PCPU-4) was prepared in the same manner as the synthesis of (PCPU-3) above, and an aqueous dispersion (PCPU-4WD) was obtained in the same manner as the preparation of (PCPU-3WD). The proportion (content) of the cyclohexane ring structure in the entire polycarbonate polyurethane (PCPU-4) was 42.7% by mass.

[0127] Synthesis of polyurethane resin (PCPU-5) and preparation of water dispersion (PCPU-5WD): Instead of dicyclohexylmethane-4,4'-diisocyanate, 4,4'-diphenylmethane diisocyanate was used, and the molar number was adjusted. Except for this, (PCPU-5) was prepared in the same manner as in the synthesis of (PCPU-2) above, and a water dispersion (PCPU-5WD) was obtained in the same manner as in the preparation of (PCPU-2WD). The proportion (content) of the cyclohexane ring structure in the entire polycarbonate polyurethane (PCPU-5) was 29.1% by mass.

[0128] Synthesis of polyurethane resin (PCPU-6) and preparation of water dispersion (PCPU-6WD): Instead of dicyclohexylmethane-4,4'-diisocyanate, 4,4'-diphenylmethane diisocyanate was used, and the molar number was adjusted. Except for this, (PCPU-6) was prepared in the same manner as in the synthesis of (PCPU-1) above, and a water dispersion (PCPU-6WD) was obtained in the same manner as in the preparation of (PCPU-1WD). The proportion (content) of the cyclohexane ring structure in the entire polycarbonate polyurethane (PCPU-6) was 0.0 mass%.

[0129] Synthesis of polyurethane resin (PCPU-7) and preparation of water dispersion (PCPU-7WD): (PCPU-7) was prepared in the same manner as in the synthesis of (PCPU-6) above, except that 4,4'-diphenylmethane diisocyanate was replaced with xylene diisocyanate and the molar number was adjusted, and a water dispersion (PCPU-7WD) was obtained in the same manner as in the preparation of (PCPU-6WD). The proportion (content) of the cyclohexane ring structure in the entire polycarbonate polyurethane (PCPU-7) was 0.0 mass%.

[0130] [Polyester resin] Preparation of polyester resin (PEs-1): A polyester resin (PEs-1) was polymerized according to a known polymerization method. The composition of the obtained polymer was as follows: 1 H-NMR analysis was performed, and the molar percentage of each component was determined from the integral ratio. The results are shown in Table 1. The reduced viscosity of the resulting polyester resin was 0.583 dl / g. The abbreviations shown in Table 1 are listed below. TPA: Terephthalic acid IPA: Isophthalic acid CHMM: Cyclohexylmethylmalonate DSS: Dimethyl-5-sodium sulfoisophthalate EG: Ethylene glycol HD: Hexanediol DEG: Diethylene glycol CHDM: 1,4-cyclohexanedimethanol

[0131] Preparation of polyester water dispersion (PEs-1WD): In a reactor equipped with a stirrer, thermometer, and reflux device, 30 parts by mass of copolymerized polyester resin (PEs-1) and 15 parts by mass of ethylene glycol-n-butyl ether were placed, and the resin was dissolved by heating and stirring at 110°C. After the resin was completely dissolved, 55 parts by mass of water was gradually added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to produce a milky white polyester resin (PEs-1) aqueous dispersion (PEs-1WD) with a solid content of 25.1% by mass. The liquid viscosity of the resulting aqueous dispersion was 84 mPa·s.

[0132] Production of polyester resins (PEs-2 to PEs-4): Similar to the polymerization of the polyester resin (PEs-1) described above, polyester resins (PEs-2), (PEs-3), and (PEs-4) were produced according to a known polymerization method. As with PEs-1, the composition ratio was determined and the reduced viscosity of the resulting resin was evaluated. The results are shown in Table 1.

[0133] Preparation of polyester water dispersions (PEs-2WD to PEs-4WD): Polyester water dispersions (PEs-2WD), (PEs-3WD), and (PEs-4WD) were prepared in the same manner as in the preparation of the polyester water dispersion (PEs-1WD) described above. The solid content and liquid viscosity were evaluated in the same manner as in the case of PEs-1WD. The results are shown in Table 2.

[0134] [Table 1]

[0135] [Table 2]

[0136] [Crosslinking agent] Preparation of water dispersion (C-1WD) of blocked isocyanate-based crosslinking agent (C-1): In a flask equipped with a stirrer, thermometer, and reflux condenser, 125.2 parts by mass of a polyisocyanate compound having a biuret structure made from hexamethylene diisocyanate (Asahi Kasei Chemicals, Duranate 24A-100, NCO concentration 23.1%), 50.0 parts by mass of dipropylene glycol dimethyl ether, and 68.8 parts by mass of 3,5-dimethylpyrazole were added, and the mixture was stirred at 70°C under a nitrogen atmosphere for 2 hours. The infrared spectrum of the reaction solution was then measured, and it was confirmed that the absorption of the isocyanate group had disappeared. Next, after cooling to room temperature, 6 parts by mass of polyethylene glycol (n=12) monolaurate was added, and the mixture was stirred for 2000 min. -1 Water was added while stirring and mixing at 40° C. The concentration was adjusted with water to prepare an aqueous dispersion (C-1WD) of the blocked isocyanate-based crosslinking agent (C-1) having a solid content of 30.0% by mass.

[0137] Preparation of water dispersion (C-2WD) of blocked isocyanate-based crosslinking agent (C-2): In a flask equipped with a stirrer, a thermometer, and a reflux condenser, 100 parts by mass of a polyisocyanate compound having an isocyanurate structure prepared from 1,6-hexamethylene diisocyanate by an existing method (Asahi Kasei Chemicals, Duranate TPA-100, NCO concentration 23.1%), 17.5 parts by mass of N-methylpyrrolidone, and 35.00 parts by mass of 3,5-dimethylpyrazole were dropped, and the mixture was kept at 70 ° C. for 1 hour under a nitrogen atmosphere. Then, 12.50 parts by mass of dimethylolpropionic acid were dropped. The infrared spectrum of the reaction solution was measured, and after confirming that the absorption of the isocyanate group had disappeared, 8.72 parts by mass of N,N-dimethylethanolamine was added. After stirring for 1 hour, an appropriate amount of water was added to prepare an aqueous dispersion (C-2WD) of a blocked isocyanate-based crosslinking agent (C-2) with a solid content of 30.0% by mass.

[0138] [Example 1] (Preparation of Coating Solution) A coating solution having the following composition was prepared. Water 43.47 parts by mass Isopropyl alcohol 30.57 parts by weight Silica sol 4.15 parts by mass (Silica sol with an average particle size of 100 nm, solid content concentration of 10.5% by mass) PCPU-1WD 5.42 parts by mass (Solid content concentration 25.0% by mass) PEs-1WD 7.58 parts by mass (Solid content concentration 25.1% by mass) C-1WD 8.43 parts by mass (Solid content concentration 30.0% by mass) Surfactant 0.05 parts by weight (Silicone-based, solid content 10.0% by mass) High boiling point solvent 0.34 parts by mass

[0139] (Production of Highly Adhesive Polyester Film) As the raw polymer for the film, PET resin pellets having an intrinsic viscosity of 0.62 dl / g (solvent: phenol / tetrachloroethane = 60 / 40) and substantially free of particles were dried at 135°C for 6 hours under a reduced pressure of 133 Pa. Then, the pellets were fed to an extruder, melt-extruded into a sheet at about 280°C, and rapidly cooled and solidified on a rotating cooling metal roll maintained at a surface temperature of 20°C to obtain an unstretched PET sheet.

[0140] Next, the above coating solution was applied to one side of a PET film by roll coating, and then dried at 80°C. After final stretching, the coating amount after drying was 0.12 g / m 2 The film was then stretched 4.0 times in the width direction at 150°C in a tenter, heated at 230°C while the length of the film in the width direction was fixed, and then subjected to a relaxation treatment in the width direction at 230°C to obtain a highly adhesive polyester film having a thickness of 50 μm.

[0141] The thickness of the adhesive coating layer of the obtained adhesive polyester film was 79 nm, and the film haze was 0.54%.

[0142] Next, a functional layer-forming coating liquid (coating liquids L and M for forming a hard coat layer described in (4) above, and coating liquid N for forming a photocurable adhesive layer described in (5) above) was used on the highly adhesive coating layer of the highly adhesive polyester film, and a laminated polyester film having a functional layer was obtained according to the formation method described above.

[0143] When the adhesion of the functional layer of the obtained laminated polyester film was evaluated, the adhesion strength X was 96%.

[0144] On the other hand, the above-mentioned easy-adhesive polyester film was left in a high-temperature and high-humidity tank under an environment of 80°C and 90 RH% for 24 hours, and then left at room temperature for 12 hours. After that, a functional layer was formed on the easy-adhesive coating layer of the treated easy-adhesive polyester film using the functional layer-forming coating liquid (same as above), to obtain a laminated polyester film.

[0145] When the adhesion of the functional layer of this laminated polyester film was evaluated, the adhesion strength Y was 95%.

[0146] From this result, XY=1(%). These results are shown in Table 3.

[0147] The above-mentioned adhesive polyester film that was not subjected to high temperature and high humidity treatment was rolled up and left for 6 months in an environment of temperature: 0°C to 30°C and humidity: 10% RH to 80% RH. After leaving the roll, a sample of the adhesive polyester film was taken and the adhesion was evaluated in the same manner as above.

[0148] The evaluation results of the adhesion of the samples from the roll (adhesion Z) are shown in Table 3. Regarding the adhesion reliability based on these results, samples that could ensure 100% or more adhesion were rated as "A", samples that could ensure adhesion of 95% or more but less than 100% were rated as "B", samples that could ensure adhesion of 90% or more but less than 95% were rated as "C", and samples that had less than 90% adhesion were rated as "D". The evaluation results of adhesion reliability are shown in the adhesion reliability column in Table 3. Samples that could ensure adhesion of 90% or more for Z can be confirmed as having ensured adhesion reliability.

[0149] As a result of the evaluation, the adhesion Z was 92%, which resulted in the adhesion reliability being rated "C" and it was determined that the adhesion reliability was guaranteed.

[0150] [Examples 2 and 3] Except for changing the thickness of the coating solution to that shown in Table 3, the same procedure as in Example 1 was carried out to obtain an easily adhesive polyester film.

[0151] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film having a functional layer was obtained in the same manner as in Example 1. The various evaluation results are shown in Table 3.

[0152] [Examples 4 to 17] A highly adhesive polyester film was obtained in the same manner as in Example 1, except that the polycarbonate polyurethane resin and polyester resin used were changed to the combination shown in Table 3.

[0153] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film having a functional layer was obtained in the same manner as in Example 1. The various evaluation results are shown in Table 3.

[0154] [Example 18] An easily adhesive polyester film was obtained in the same manner as in Example 1, except that the crosslinking agent used was changed to C-2WD.

[0155] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film having a functional layer was obtained in the same manner as in Example 1. The various evaluation results are shown in Table 3.

[0156] [Examples 19 to 20] The same evaluations as in Example 1 were carried out except that the functional layers shown in Table 3 were added to the highly adhesive polyester film produced in the same manner as in Example 1. The various evaluation results are as shown in Table 3.

[0157] [Comparative Examples 1 to 10] A highly adhesive polyester film was obtained in the same manner as in Example 1, except that the polycarbonate polyurethane resin and polyester resin used were changed to the combination shown in Table 3.

[0158] The obtained highly adhesive polyester film was evaluated in the same manner as in Example 1, and then a laminated polyester film having a functional layer was obtained in the same manner as in Example 1. The various evaluation results are shown in Table 3.

[0159] [Table 3] [Industrial Applicability]

[0160] The highly adhesive polyester film of the present invention has excellent adhesion between the functional layer and the polyester film (especially adhesion after long-term storage, etc.) and has high adhesion reliability. It also has excellent blocking resistance and transparency. Therefore, it can be widely used in optical applications, etc.

Claims

1. The present invention provides an easily adhesive polyester film having a polyester film substrate and a coating layer on at least one side thereof, the coating layer being formed from a composition containing a polycarbonate polyurethane resin, a polyester resin and inert particles, the polycarbonate polyurethane resin and the polyester resin both containing a cyclohexane ring in their respective molecules and having a structure in which at least one hydrogen atom on the cyclohexane ring is substituted with a hydrocarbon group.

2. The polycarbonate polyurethane resin is an addition reaction product of a polycarbonate diol component and a diisocyanate component, or an addition reaction product of a polycarbonate diol component, a diisocyanate component and a diol component as a chain extender, and at least one of the components contains a cyclohexane ring.

3. The highly adhesive polyester film according to claim 1 , wherein the inert particles are inorganic particles.

4. 2. The highly adhesive polyester film according to claim 1, wherein the inert particles have an average particle size of 0.04 to 2.0 μm.

5. The highly adhesive polyester film according to claim 1, wherein the content of the cyclohexane ring structure in the polycarbonate polyurethane resin is 5 to 55% by mass, and the content of the cyclohexane ring structure in the polyester resin is 5 to 20% by mass.

6. A laminated polyester film comprising a functional layer on the coating layer of the highly adhesive polyester film according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Laminated polyester film for molding

    JP2010131767A

  • Easy adhesive polyester film

    JP2011126066A

  • Highly adhesive thermoplastic resin film

    JP2011153290A

  • Easily-adhesive optical polyester film

    JP2011168053A

  • Laminated polyester film

    JP2011246663A